Advances in Reproduction, Nutrition and Disease Research in the Yellowtail Kingfish ( Seriola lalandi ) Aquaculture - Alejandro S. Mechaly; Abigail Elizur; Sebastian Escobar‐Aguirre; Jorge Hirt‐Chabbert; Roxana Bertha Inohuye‐Rivera; Wayne Knibb; Josephine Nocillado; Juan C. Pérez‐Urbiola; H. K. A. Premachandra; Gustavo M. Somoza; Dariel Tovar‐Ramírez; Bin Wang (Reviews in Aquaculture, 2025)
Yellowtail kingfish ( Seriola lalandi ) is a species of significant value in aquaculture, with a broad distribution across subtropical and temperate seas. Although global production has doubled in 7 years, reaching approximately 9000 tons per year in 2021, its cultivation remains limited compared to other mainstream species. The commercial aquaculture of this species faces several key challenges in achieving improved production and sustainability: nutrition requirements, disease management, and the optimization of reproductive technologies. Current diets for yellowtail kingfish require further improvement to enhance both growth performance and sustainability. Diseases continue to be a major constraint, with at least 41 specific diseases reported for yellowtail kingfish and 31 affecting other Seriola species, emphasizing the necessity of targeted diagnostic tools and treatment strategies. Recent genomic advances have shed light on the biology and taxonomy of yellowtail kingfish, revealing genetically distinct populations across the South Pacific, Indian, and South Atlantic Oceans. However, the taxonomic status within the Pacific region remains unclear, requiring further research. Addressing these gaps is vital for developing robust breeding programs and improving genetic resilience. To support the sustainable expansion of yellowtail kingfish aquaculture, key areas for future research include increasing larval and juvenile survival rates, minimizing malformations, and tailoring farming models to diverse environmental conditions. Focusing on these priorities will ensure better productivity and disease resistance, ultimately promoting the global competitiveness of yellowtail kingfish as an aquaculture species.